SISTEM INFORMASI GEOGRAFIS LOKASI DESA TANGGUH BENCANA (DESTANA) BERBASIS ANDROID PADA BADAN PENANGGULANGAN BENCANA DAERAH KABUPATEN GORONTALO - Arya Pakaya (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2020)
Tangguh Disaster Village is a village that has a self-reliant ability to adapt and face disaster threats and recover immediately from adverse catastrophic impacts. The problem in designing this system is that there is no geographical information system based on Android in the process of searching the data location of Tangguh disaster Village (DESTANA) in Gorontalo district. This research aims to design an Android-based geographic information system that can be used to locate the Tangguh Disaster village (DESTANA) data location in Gorontalo District to help local people and migrants with Use Android mobile devices that provide information about the Tangguh disaster Village (DESTANA) data location and know the location of an area presented with digital map facilities.Â The results of the study concluded that the test results to search for the location information of disaster Tangguh Village (DESTANA) and display the appropriate and valid view so that the application can be used effectively and efficiently.